Regional Unemployment and Job Switches in Germany – An Analysis at District Level - Antje Mertens; Anette Haas (European Regional Science Association (ERSA), 2005)
The role of mobility is central to the debate on reducing unemployment. A further question is to what extent a lack of mobility enforces regional disparities. Using a micro data set containing information about two cohorts we analyse the impact of regional unemployment at district level to regional employment duration. As an alternative to the frequently used Logit analysis approach we focus to duration time analyses. We use Cox Regression (Breslow Method for ties) and Piece wise constant models to find out the impact of regional unemployment rate for duration working in a special region. Additionally we could differentiate between voluntary and involuntary mobility. The results of this comparison show a contrary influence of the regional unemployment rate. Our results confirm the lower mobility of woman and that the younger cohort exhibits higher mobility rates. We also compare downward/upward moves (defined as wage losses/gains after mobility) and could not find evidence for influence of regional unemployment rate to wage growth. This yields us to the conclusion that high levels of regional unemployment inhibit mobility because of a lack of vacancies.
Keywords: 330